TOXICANTS IN OILS FOR CONTROL OF THE CITRUS BLACKFLY - SHAW, JG; PLUMMER, CC (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1949)
The classification is offered under 2 major headings (1) General classification of tumors (2) Special classification of neoplasms according to the organs and systems involved The classifications bear considerable resemblance to that presented in the St
J FERMENT TECHNOL
Keywords: TOXICANTS, OILS, CONTROL, CITRUS BLACKFLY; CIENCIAS DE LA VIDA; BIOLOGIA DE INSECTOS; ENTOMOLOGIA GENERAL